2023
DOI: 10.1002/jia2.26059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influences of diabetes and prediabetes among adults living with HIV in Africa: a systematic review and meta‐analysis

Abstract: Introduction:In people living with human immunodeficiency virus (PLHIV), traditional cardiovascular risk factors, exposure to HIV per se and antiretroviral therapy (ART) are assumed to contribute to cardiometabolic diseases. Nevertheless, controversy exists on the relationship of HIV and ART with diabetes. To clarify the relationship between HIV and type 2 diabetes, this review determined, in PLHIV in Africa, diabetes and prediabetes prevalence, and the extent to which their relationship was modified by socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…However in SSA, PWH who are on ART, including older-generation thymidine analogues and protease inhibitors, appear to have comparable 15, 16 if not better 17, 18, 19 glucose metabolism profiles than the general population. While this may be attributed to insufficient research in SSA, especially the dearth of longitudinal studies with incidence measures 20 , physiological adaptations in PWH in SSA that potentially protect against cardiometabolic disease, including diabetes, have not been considered.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However in SSA, PWH who are on ART, including older-generation thymidine analogues and protease inhibitors, appear to have comparable 15, 16 if not better 17, 18, 19 glucose metabolism profiles than the general population. While this may be attributed to insufficient research in SSA, especially the dearth of longitudinal studies with incidence measures 20 , physiological adaptations in PWH in SSA that potentially protect against cardiometabolic disease, including diabetes, have not been considered.…”
Section: Introductionmentioning
confidence: 93%
“…31, 32 This includes central obesity, with or without lipodystrophy, both significant determinants of prevalent and new-onset diabetes. 31 It is the nexus of these factors, i.e., HIV, ART metabolic side effects, excess weight gain and an obesogenic environment, that is believed to drive excess diabetes risk in persons PWH in HICs 10, 11, 12 whereas its occurrence in SSA 17, 18, 33 , is yet to be mirrored in an excess burden of diabetes in the population of PWH.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension afflicts 8.9 million PLHIV globally, and, while prevalence varies by region, it affects nearly 20% of all PLHIV in Eastern and Southern Africa [ 6 , 7 ]. Similarly, cardiometabolic complications related to diabetes are increasing among PLHIV in Zambia and the region [ 8 ], with prevalence estimates exceeding 5% and 15% for diabetes mellitus and prediabetes, respectively [ 9 ]. Diabetes mellitus among PLHIV is associated with 2.4 times the risk of CVD events compared to HIV-uninfected persons [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa not only has challenges with an increasing burden of T2D, but it is also the world's epicenter of HIV infections, accounting for more than 70% of the infections, with the numbers of those >50 years living with HIV estimated to triple by 2040 [ 21-23 ]. While earlier studies indicate a higher likelihood of impaired glucose metabolism among people living with HIV compared to those without HIV [ 24-26 ], more recent studies from SSA report inconsistent findings, particularly in the context of newer antiretroviral therapies (ART) [ 27 , 28 ]. Some studies have reported increased risk of diabetes [ 27 , 28 ] and others no association of HIV and ART and prevalent diabetes [ 29-31 ].…”
mentioning
confidence: 99%
“…While earlier studies indicate a higher likelihood of impaired glucose metabolism among people living with HIV compared to those without HIV [ 24-26 ], more recent studies from SSA report inconsistent findings, particularly in the context of newer antiretroviral therapies (ART) [ 27 , 28 ]. Some studies have reported increased risk of diabetes [ 27 , 28 ] and others no association of HIV and ART and prevalent diabetes [ 29-31 ]. Notably, studies in the United States have reported that hypogonadism is common among men living with HIV (MLWH) despite effective ART [ 1 , 3 ].…”
mentioning
confidence: 99%